Identifikasi Komptensi Pustakawan Digital Berdasarkan Analisis Pekerjaan Pustakawan dari Tahun 2016-2018 di Indonesia - Arwendria Arwendria (UIN Imam Bonjol Padang, 2019)
New information environment requires modern skills and librarians must adapt to the new environment (Chinien and Boutin, 2011). In the digital information environment, librarians need to acquire digital competencies (Graham, 2003), because they are responsible for building digital libraries for their readers (Seshaiah and Veeraanjaneyulu, 2009). However, the results of the study indicate that university library in Indonesia haven’t moved quickly to digital libraries, so that the competence of digital librarians is only a small part of needed. Librarianship in Indonesia is still moving from the traditional library towards the hybrid library. On the other hand, these developments must be addressed by the organizers of library science courses to be able to prepare librarian candidates capable of managing digital libraries.